ПЕРЕДУМОВИ ТРАНСФОРМАЦІЇ СИСТЕМИ МОТИВАЦІЇ МЕДИЧНОГО ПЕРСОНАЛУ В УМОВАХ РЕФОРМУВАННЯ СИСТЕМИ ОХОРОНИ ЗДОРОВ`Я ТА ВОЄННОГО СТАНУ В УКРАЇНІ - Яна КОЛЕСНИК (Herald of Khmelnytskyi National University. Economic sciences, 2026)
The full-scale war has significantly affected Ukraine’s healthcare system and the working conditions of healthcare professionals. Medical personnel operate under increased workloads, staff shortages, psychological stress, and security risks. Additional challenges have emerged for healthcare workers who were forced to relocate due to hostilities and continue their professional activities in other regions of the country. Under such circumstances, the issue of motivation becomes particularly relevant. The aim of this study is to analyze current scientific evidence regarding the factors influencing healthcare personnel motivation in the context of healthcare reform and martial law. Based on a review of scientific literature, the main socio-economic, professional, organizational, and psychosocial factors affecting the motivation of healthcare workers were identified. Particular attention is paid to the impact of housing conditions, financial stability, professional development opportunities, support from management and colleagues, as well as the consequences of forced displacement. The results of the analysis indicate the need to improve approaches to healthcare personnel management, taking into account the new challenges associated with martial law.